Characterizing cloud cover and satellite revisit with cloud masks in North West England - Ogunbadewa, Ebenezer Yemi (Geodesy and Cartography, 2012)
The aim of this study is to determine the availability of cloud-free images in relation to satellite revisit periods for the UK and in particular for the North West of England. Cloud cover was analysed with cloud masks from AVHRR/APOLLO and TERRA/MODIS cloud products. Availability of cloud-free images was determined from revisit frequency and the numbers of monthly images from Landsat ETM+, ASTER, Quickbird and SPOT satellite sensor series. The average number of cloud-free days at Risley Moss and Charter's Moss is five days per month with a minimum of one cloud-free day. The results show that satellite revisit periods and cloud cover are major determinants of satellite data availability and in this study it was also found that contrary to popular opinion, satellite overpass does not necessarily mean imaging opportunity and additional cloud-free images could be obtained when there are no satellite overpasses. The numbers of cloud-free images at a given site may be increased by combining data from different satellite sensors.